THE METAPHOR OF SWOBODA IN THE TREATIES OF THE EUROPEAN UNION - LIZISOWA, Maria Teresa (Comparative Legilinguistics, 2012)
The subject of this article is a linguistic analysis of the texts of the EU Treaty of 1992, as well as of the Treaty on the Functioning of the EU of 2010, with an aim to demonstrate that in these legislative acts the meanings of legal and economic terms are communicated through the means of everyday expressions, which in great measure retrace the practical way of human thinking. The author claims that in legal principles regarding the decisions about the stability of the financial market, the metaphor of swoboda (Eng. freedom) enables to understand the abstract sphere of the creating and functioning of the European economy in the image schemas of “obejmowanie i wnoszenie”, typical for material objects. The freedom of establishment is conceptualized as a person, who obejmuje (‘otacza rękami’; Eng.: ‘takes into their arms’) prawo (Eng.: law), zniesienie dyskryminacji (Eng.: abolition of any discrimination), działalność gospodarczą (Eng.: establishment), as well as wnosi (‘umieszcza wraz z sobą w czymś’; Eng.: brings [in], ‘places somewhere together with itself’) korzystny wkład w rozwój produkcji i handlu (Eng.: valuable contribution to the development of production and trade). In the metaphor of swoboda are inscribed the metaphors of the EU market in the image schemas of “przepływ [ruch]” (Eng.: ‘flow’, ‘movement’), “obrót” (Eng.: ‘circulation’) and “sojusz” (Eng.: ‘alliance”). In the Polish translation of the Treaties, economic goods are treated as if they were a liquid [płyn], protected due to their expected profit; and the transfer of money, services and people producing these goods is described as przepływ [flow] of the goods. In the English text of the Treaties inflow refers only to persons, while the transfer of money, goods and services is referred to as movement [ruch]. An alternative metaphorical pattern in both the Polish and English languages is created by obrót [circulation]. These metaphors are linked to the metaphor of the market as a container, in which swoboda [freedom] locates the movement [flow] and the circulation of goods, services, money and persons. In the EU Treatises, the economic cooperation is depicted as a military alliance [sojusz wojenny] in relation to the struggle for the market [walka o rynek], in the economic discourse. The metaphorical patterning depicts the personified swoboda [freedom], sub-dependent to which are the ontological and orienteering metaphors communicating the principles of the functioning of the internal EU market. Summing up, the author concludes that in the Polish translation of the EU Treaties the notions of swoboda and wolność are separated, because the word wolność is used in its literal meaning in the Preamble to the Treatises, so within the axiological principle of law, whereas in the regulations of these legislative acts, the word swoboda, used metaphorically, characterises the aspect of establishment as a principle-norm to which, in the legal regulations of these legislative acts, all the other norms are sub-dependent. In the English version such a strong polarisation of meanings does not occur.